1997
DOI: 10.2307/3870440
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the C 4 Me1 Gene from Flaveria bidentis Requires an Interaction between 5' and 3' Sequences

Abstract: The efficient functioning of C4 photosynthesis requires the strict compartmentation of a suite of enzymes in either mesophyll or bundle sheath cells. To determine the mechanism controlling bundle sheath cell-specific expression of the NADP-malic enzyme, we made a set of chimeric constructs using the 5[prime] and 3[prime] regions of the Flaveria bidentis Me1 gene fused to the [beta]-glucuronidase gusA reporter gene. The pattern of GUS activity in stably transformed F. bidentis plants was analyzed by histochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
21
2

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 0 publications
3
21
2
Order By: Relevance
“…The evolution of C 4 photosynthesis from the C 3 ancestral state requires mechanisms generating increased abundance as well as cell specificity of a large number of enzymes (Marshall et al, 1997;Patel et al, 2004;Gowik et al, 2004;Wiludda et al, 2012). A recent study has suggested that the evolution of increased abundance can be complex, with multiple sequences within promoters and 59 UTRs contributing to the expression of C 4 genes (Wiludda et al, 2012).…”
Section: Discussion Evolutionary Events Underlying the Recruitment Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…The evolution of C 4 photosynthesis from the C 3 ancestral state requires mechanisms generating increased abundance as well as cell specificity of a large number of enzymes (Marshall et al, 1997;Patel et al, 2004;Gowik et al, 2004;Wiludda et al, 2012). A recent study has suggested that the evolution of increased abundance can be complex, with multiple sequences within promoters and 59 UTRs contributing to the expression of C 4 genes (Wiludda et al, 2012).…”
Section: Discussion Evolutionary Events Underlying the Recruitment Ofmentioning
confidence: 99%
“…As these studies focused on a number of genes isolated from phylogenetically distinct C 4 species, they suggest that the mechanisms regulating genes of the C 4 pathway vary both within and between independent C 4 lineages. In the majority of cases, different sequences generate increased abundance and cell specificity for the same gene (Marshall et al, 1997;Akyildiz et al, 2007;Kajala et al, 2012;Wiludda et al, 2012), suggesting that the evolution of these two traits is not coordinated. Most mechanisms identified to date are also unique to each C 4 lineage studied, although a homologous mechanism has been co-opted to generate BS specificity for multiple genes encoding malic enzyme within maize (Zea mays) and Gynandropsis gynandra (formerly designated as Cleome gynandra; Brown et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that mesophyll-specific expression of C 4 cycle genes is mainly regulated at the transcriptional level (Schaffner and Sheen, 1992;Stockhaus et al, 1994;Rosche et al, 1998;Sheen, 1999), whereas bundle-sheath-specific expression is controlled at both transcriptional and posttranscriptional levels (Long and Berry, 1996;Marshall et al, 1997;Sheen, 1999;Patel et al, 2006).…”
mentioning
confidence: 99%
“…leaves, respectively (Marshall et al, 1997). Thus, at least two chloroplastic forms of NADP-ME might be expected to occur in Flaveria spp.…”
mentioning
confidence: 99%